Computational comparison of two new fusion proteins for multiple sclerosis - Nasrin Payab; Karim Mahnam; Mostafa Shakhsi-Niaei (Wolters Kluwer Medknow Publications, 2018)
Multiple sclerosis (MS), as one of the human autoimmune diseases, demyelinates the neurons of the central nervous system (CNS). Activation of the T cells which target the CNS antigens is the first autoimmune event in MS. Myelin oligodendrocyte glycoprotein (MOG) and myelin basic protein (MBP) are two proteins of the myelin sheath and have been shown to be among the high antigens contributing to the pathogenesis of MS. Production of the drugs with high specificity for the immune system diseases is a concern for various researchers. Therefore, tolerogenic vaccines are considered as a new strategy for the treatment of MS by presenting specific antigens. This study aimed to design and compare two fusion proteins by a combination of two neuroantigens linked to interleukin-16 (IL-16) (MOG-Linker-MBP-IL16 and MBP-Linker-MOG-IL16) as vaccines for MS. In this study, at first two models MOG (aa 11-30) linked to MBP (aa 13-32) was made by Modeler 9.10 and simulated for 20 ns via Gromacs 5.1.1 package. Then simulated antigen domains connected to the N-terminal domain of IL-16 and obtained structures simulated for 50 ns. The results revealed that both constructs had stable structures and the linker could keep two antigenic fragments separate enough, preventing undesired interactions. While MOG-Linker-MBP-IL16 showed better solubility, more accessible surface areas, more flexibility of its IL-16 domain, and better functionality of its IL-16 domain as well as more specific cleavage of its related epitopes after endocytosis lead to a better presentation of its antigenic property.